2017
DOI: 10.3390/gels3020014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chitosan Molecular Weight and Attached Non-Interactive Chains on the Formation of α-Lactalbumin Nanogel Particles

Abstract: Thermal treatment of protein-polysaccharide complexes will form nanogel particles, wherein the polysaccharide controls nanogel formation by limiting protein aggregation. To determine the impact of the chitosan molecular weight and non-interactive chains on the formation of nanogels, mixtures of α-lactalbumin were prepared with selectively-hydrolyzed chitosan containing covalently-attached polyethylene glycol chains (PEG) and heated near the protein's isoelectric point to induce formation of nanogels. Turbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…25,30 Therefore, the change of ζ potential from negative to positive demonstrated that α-la molecules were surrounded by chitosan molecules. Similar results have been observed in the research of Du et al 31 For the sample with an α-la/chitosan ratio of 5:1, α-la/chitosan complexes had an average ζ potential of +21 ± 2 mV. With a further increase of chitosan addition to a ratio of 2:1, the formed complexes had a much higher ζ potential value of +33 ± 2 mV, which was similar to pure chitosan, indicating that the surface of α-la molecules was fully surrounded by chitosan molecules.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…25,30 Therefore, the change of ζ potential from negative to positive demonstrated that α-la molecules were surrounded by chitosan molecules. Similar results have been observed in the research of Du et al 31 For the sample with an α-la/chitosan ratio of 5:1, α-la/chitosan complexes had an average ζ potential of +21 ± 2 mV. With a further increase of chitosan addition to a ratio of 2:1, the formed complexes had a much higher ζ potential value of +33 ± 2 mV, which was similar to pure chitosan, indicating that the surface of α-la molecules was fully surrounded by chitosan molecules.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The addition of chitosan significantly increased the size to a maximum value of 810 ± 33 nm at a ratio of 5:1, which was due to the bridging effect of chitosan. It is important to note that the α-la/chitosan complexes formed at pH > 5.0 were reported to be insoluble, , which could be confirmed by results from optical appearance and turbidity. The decreased size with an increasing temperature indicated that heating promoted the formation of α-la/chitosan aggregates.…”
Section: Resultsmentioning
confidence: 62%